Niobium carbide as a technology demonstrator of ultra‐high temperature ceramics for fully ceramic microencapsulated fuels. Issue 2 (18th July 2019) - Ang, Caen; Snead, Lance; Benensky, Kelsa
Abstract: The consolidation of Fully Ceramic Microencapsulated (FCM) fuels has been extended from matrices based on SiC to ultra‐high temperature ceramics (UHTCs). Specifically, sintering conditions of NbC1‐x were compatible with hosting of microencapsulated fuel. NbC powder in as‐received, chemically treated, and composite forms was consolidated. Elemental analysis, shrinkage of powder compacts, contents of ejected vapor, density, microstructure, and NbC lattice constants were analyzed. As‐received NbC showed more shrinkage due to the presence of a liquid phase compared with the chemically treated powder. Removal of impurity metals was observed from chemical treatment and during sintering of as‐received powders. An increase in true density during sintering was attributed to removal of compounds with lower density than NbC. Chemically treated powder showed reduced densification rate and absence of a liquid phase after sintering. Smaller grain sizes were observed in the NbC composite. The implications for NbC and other binary carbides as matrices for FCM fuels are discussed. Abstract : Surrogate fuel microspheres compacted and sintered in a UHTC matrix under conditions compatible with FCM fabrication.